Engineering plastics handbook - Margolis, James M. (McGraw-Hill, 2006)
complete single-volume reference, the Handbook covers the essential chemical, physical, mechanical, and applications aspects of many of the most important thermoplastics, providing researchers with the data necessary to evaluate and compare existing product lines with new and emerging ones. Readers will also find a detailed approach for evaluating some of the most recent breakthroughs, such as: Chemistry of Polymerization; Products and Designs Based on Viscoelasticity; Processes